2012
DOI: 10.1007/s00268-012-1747-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated Irradiation with 3 Cycles of Induction Chemotherapy in Stage IIIA‐N2 Lung Cancer

Abstract: This trimodal therapy was effective and well tolerated, and it is an acceptable therapeutic option for patients with locally advanced stage IIIA-N2 NSCLC. Patients without persistent multiple-station N2 showed promising survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In terms of tumor histology, a significantly higher percentage of patients with squamous cell carcinoma had Ef2 or Ef3 than those with non-squamous cell carcinoma (85.1% vs. 59.3%, P=0.018). Similar results have been reported previously (12). The mechanism underlying this result is unclear, however, and further investigation is required.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of tumor histology, a significantly higher percentage of patients with squamous cell carcinoma had Ef2 or Ef3 than those with non-squamous cell carcinoma (85.1% vs. 59.3%, P=0.018). Similar results have been reported previously (12). The mechanism underlying this result is unclear, however, and further investigation is required.…”
Section: Figuresupporting
confidence: 90%
“…Another approach is to administer induction chemotherapy or chemoradiotherapy (ICRT) before the surgical procedure in order to control microscopic metastases and render the tumor completely resectable. Some analyses have demonstrated that ICRT improved the pathological complete response (CR) and local control rates in comparison to chemotherapy alone (10)(11)(12)(13)(14). ICRT has the potential to reduce the tumor size, achieve complete resection, eradicate micrometastases, and extract occult metastasis by performing a re-staging examination after ICRT (15).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that prognosis of patients with advanced nonsmall cell lung cancer (NSCLC), especially stage IIIA NSCLC patients with mediastinal lymph node metastasis, can be improved using multimodal therapy . However, cancer progression during chemotherapy or relapse after postoperative therapy often occurs probably because of the induction of chemoresistance through some mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…43 The management of these patients was based on the data from phase III trials for unresectable locally advanced NSCLC, which suggest that a combination of a platinum and third-generation anti-cancer agent with concurrent radiation may become established as the standard treatment for this population. [43][44][45][46][47][48][49] Of note, while a retrospective study 49 has suggested the superiority of chemoradiotherapy over chemotherapy in the induction setting, this result has not been demonstrated prospectively, because randomized studies to compare these two approaches had to be terminated due to the lack of interested participants (Radiation Therapy Oncology Group-0412) or slow accrual (The West Japan Thoracic Oncology Group-9903). 50,51 The Lung Intergroup Trial 0139 was performed as a large randomized phase III trial for mainly resectable N2 disease, but failed to demonstrate the benefit of addition of surgery after chemoradiotherapy in the entire population with 5-year OS of 27.2% and 20.3% in patients treated by induction chemoradiotherapy followed by surgery or by definitive chemoradiotherapy, respectively.…”
Section: Management Of Nsclc With Mediastinal Lymph Node Metastasismentioning
confidence: 99%